A New Method for the Quality of Service Assessment of Highly Frequented Bicycle Facilities in Germany. Issue 2 (February 2023) - Brandenburg, Alexander; Geistefeldt, Justin; Zeidler, Verena; Buck, Sebastian; Vortisch, Peter; Baier, Michael M.
Owing to increasing bicycle traffic volumes in Germany, more and more bicycle facilities are being designed with widths beyond the standard values given in the existing design guidelines. However, the level of service assessment method for bicycle facilities in the current edition of the German Highway Capacity Manual, HBS, is based on empirical data from facilities with mostly low traffic demand and small widths. Therefore, a new quality of service assessment method for highly frequented bicycle facilities was developed. For this, the cycling behavior of cyclists at high traffic volumes was analyzed, considering different bicycle types. Bicycle traffic flow quality, which is mainly characterized by the ability for cyclists to pass, was examined on segments of bicycle facilities with different geometric parameters, including facility type, gradient, and width. The speed and lateral distance behavior of cyclists were analyzed by using radar and video measurements. It was found that a large variance in the bicycle speed distribution mainly resulted from an inhomogeneous composition of bicycle types. The bicycle facilities were modeled with the microscopic traffic simulation tool PTV Vissim and calibrated using the empirical data. The models were used to analyze the impact of different geometric parameters and high proportions of specific bicycle types. As expected, the simulations revealed that the quality of service was mainly influenced by the lane width. Based on the results, a method to assess the quality of service of bicycle facilities, in which traffic density is used as the measure of effectiveness, was developed.